Morfologia externa da operária de lestrimelitta ehrhardtti (hymenoptera: meliponini) (2010)
ABSTRACT  Workers of Lestrimelitta ehrhardtti Friese were studied based on a great number of individuals collected in Castro municipality, Paraná State, Brazil. The specimens were described morphologically, measured and illustrated. KEY-WORDS: Apidae, stingless-bees, cleptobiotic, Neotropical.   RESUMEN Se estudió un gran número de obreras de Lestrimelitta ehrhardtti Friese colectadas en el municipio de Castro, Paraná, Brasil. Los especímenes fueran descritos  morfológicamente, medidos e ilustrados. PALABRAS CLAVE: Apidae, abejas sin aguijón, cleptobiótica, Neotropical.